ROYAL MARRIAGE AND CONVERSION IN BEDE’S HISTORIA ECCLESIASTICA GENTIS ANGLORUM - MacCarron, Máirín (Journal of theological studies, 2017)
The prevailing view in modern scholarship is that Bede reduced the role of women in his narrative of Anglo-Saxon conversion, in contrast to Gregory of Tours, with whom Bede is unfavourably compared. In his account of the conversion of Clovis, king of the Franks, Gregory allowed an overt role for the king’s wife, Clotild, whereas in Bede’s presentation of mixed marriages between Christian queens and pagan kings his queens do not actively convert their husbands. This essay presents a counter-thesis, arguing that the importance of Christian queens can be detected in Bede’s Historia when attention is paid to scriptural imagery and exegetical allusions in his text. Bede’s Historia is the only early source that refers to Christian queens at pagan courts in Anglo-Saxon England, and his presentation indicates that these women fulfilled scriptural precepts such as 1 Cor. 7:14, ‘the unbelieving husband is sanctified by the believing wife’. This theological dimension reveals the unique role played by Christian queens in the conversion of their husbands and the significance of royal marriages in the acceptance of Christianity in Anglo-Saxon England.